The effect of endometriosis on placental histopathology and perinatal outcome in singleton live births resulting from IVF. Issue 4 (October 2022) - Volodarsky-Perel, Alexander; Ton Nu, Tuyet Nhung; Mashiach, Roy; Berkowitz, Elad; Balayla, Jacques; Machado-Gedeon, Alexandre; Cui, Yiming; Shaul, Jonathan; Dahan, Michael H.
Abstract: Research question: Does endometriosis have an effect on the placental histopathology pattern and perinatal outcome in singleton live births resulting from IVF treatment? Design: Retrospective cohort study evaluating the data on all live births following IVF treatment between 2009 and 2017 at one university-affiliated tertiary hospital. All patients had placentas sent for full gross and histopathology assessment, irrespective of complication status or delivery mode. The primary outcomes of the study included anatomical, inflammation, vascular malperfusion and villous maturation placental disorders. The secondary outcomes included fetal, maternal, perinatal and delivery complications. A multivariate logistic model was used to adjust the results for confounding factors potentially associated with significant placental characteristics. Results: A total of 1057 live births were included in the final analysis and were allocated to the group of women with endometriosis ( n = 75) and those without ( n = 982). After adjustment for confounding factors, endometriosis was found to be significantly associated with acute chorioamnionitis with moderate to severe maternal (odds ratio [OR] 2.2, 95% confidence interval [95% CI] 1.1–4.6) and fetal (OR 4.9, 95% CI 1.8–13.1) inflammatory response, placenta previa (OR 3.1, 95% CI 1.2–7.8), subchorionic fibrin deposition (OR 3.4, 95% CI 1.2–9.1), intervillous thrombosis (OR 3.4, 95% CI 1.5–8.1), and fetal vascular malperfusion (OR 5.1, 95% CI 1.4–18.1), as well as with preterm birth (OR 2.5, 95% CI 1.4–4.7). Conclusions: Endometriosis has a significant impact on the placental histopathology and is associated with a higher incidence of preterm birth.